PENGETAHUAN, SIKAP DAN DUKUNGAN KELUARGA TENTANG PEMANFAATAN POSBINDU PENYAKIT TIDAK MENULAR DI KRETEK BANTUL - Pipit Novita Sandra; Istika Dwi Kusumaningrum (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: PTM is a disease that is not caused by bacterial infection including degenerative chronic disease. Integrated Guidance Post (Posbindu) is one of the empowerment program that aims to increase community participation in controlling risk factors for non-communicable diseases. Based on data obtained in Dusun Tegalsari, Donotirto village, Posbindu PTM activity was attended by 30 participants from 478 people aged 15 years and still low in its utilization and participation. Objective: The purpose of this research is to know the correlation of knowledge, attitude and family support with the utilization of Posbindu PTM in Degotary Tegalsari Donotirto Village Kretek District, Bantul Regency. Method: This research type is descriptive quantitative research with cross-sectional research design. The population in this study as many as 30 people in which researchers took from the population of Degotary Tegalsari village Donotirto 15 years old and actively participate in the activities posbindu PTM. Sampling using samples saturated as many as 30 people.Instrument in this research is questionnaire by using Chi Square test. Result: The result of Chi Square test shows that there is no correlation between knowledge with the utilization of Posbindu PTM with the result of significant value (P value) the correlation between knowledge with PTM Posbindu utilization is 0.778 (P value a ). The existence of correlationbetween attitude with utilization of Posbindu PTM with result of significant value (Pvalue) equal to 0,003 (Pvalue a). The existence of correlationbetween family support with utilization of posbindu PTM with result of significant value (P value) equal to 0,001 (P value a). Conclusion: There is not significant correlation between knowledge with the utilization of Posbindu PTM, the correlation between attitude with the utilization of Posbindu PTM and family support with utilization of posbindu PTM.